Coupled convection heat transfer of water in a double pipe heat exchanger at supercritical pressures: An experimental research. (August 2019) - Wang, Qingqing; Song, Zichen; Zheng, Yulong; Yin, Yongguang; Liu, Lang; Wang, Haijun; Yao, Jianan
Highlights: Experiment about coupled heat transfer of supercritical water was conducted. Effects of three experimental variables on heat transfer were investigated. Buoyancy effect on the heat transfer was analyzed emphatically. A new heat transfer empirical correlation was proposed. Abstract: An experiment about coupled convection heat transfer of water in a double pipe heat exchanger at supercritical pressure was conducted. The effects of experimental variables on the heat transfer were investigated, and the buoyancy effect on the heat transfer of the outer pipe was analyzed emphatically. There is a difference between the peak heat transfer coefficient temperature and the pseudo-critical temperature, and the difference increases with the increase of pressure. This phenomenon is caused by the temperature gradient and the variations of thermal-physical properties in the heat transfer section. The mass flow rates of the inner pipe side and outer pipe side were always equal, and one side will offset the effect of the other side on the heat transfer. The heat transfer coefficient of the outer pipe increases with the increase of water temperature at the inlet of the inner pipe when the mean bulk temperature is lower than the pseudo-critical temperature, due to the buoyancy effect decreases at the same time. While, the buoyancy effect is almost independent of the water temperature at the inlet of the inner pipe when the mean bulk temperature is higher than the pseudo-critical temperature, due to the buoyancy effect is non-significant. A new heat transfer empirical correlation was proposed, which includes 94.01% of experimental data are within ±25% error bars.